Why do People Subtitle Movies? A Survey Research of the Subtitler Motivations and Practices - Brito , Jessica Oliveira; Guimarães , Rodrigo Laiola; Santos, Celso A. S. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
In this paper we investigate the reasons why enthusiasts dedicate time and effort to create subtitles for third-party videos shared on-line. Based on results obtained from a survey research with a community of Brazilian subtitlers, we highlight basic features of these enthusiasts as well as their motivations and main objectives. Our observations suggest that this is a volunteering and collaborative activity after all.